LAW ENFORCEMENT ON CRIMINAL ACTIONS TO PROSPECTIVE PARTICIPANTS OF HAJJ AND UMROH THROUGH DETERRENCE AND INCAPACITATION THEORY APPROACH - Kurniawan, Kukuh Dwi; Esfandiari, Fitria (Ahkam: Jurnal Hukum Islam, 2021)
The Indonesian government opens the involvement of the private sector in organizing the Hajj and Umrah pilgrimages. High public interest for Umrah has the potential to cause legal problems if it is not managed properly. There have been many cases of fraud under the guise of an umrah service organizer, demanding a real legal action breakthrough. The method used in this research is the normative research method. This paper aims to analyze, through the use of the theoretical paradigm of Deterrence and Incapacitation, which is expected to be able to affirm legal solutions that can prevent criminal acts from occurring and provide a deterrent effect to the perpetrators. The results of this study indicate that in the process of law enforcement against fraudulent acts of Hajj and Umrah pilgrims in Indonesia, various weaknesses and shortcomings are still found. This is reviewed starting from the root of the problem, law enforcement factors, the investigation process to the formulation of criminal arrangements that are not sufficient for upholding law and justice against the phenomenon of fraudulent acts of prospective Hajj and Umrah pilgrims.